The Impact of Interactive Teaching Methods on Students’ English Learning Interest Mediated by Learning Motivation - Nurmala, Ira; Kurniawan, Fajar (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study examines the effect of Interactive Teaching Style on students’ Interest in Learning English, both directly and indirectly through Learning Motivation. Using a quantitative cross-sectional survey in 2024, data were collected from 84 students across five study programs, selected through simple random sampling. The relationships among variables were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings indicate that Interactive Teaching Style positively and significantly affects Interest in Learning English (? = 0.4032, T = 2.9560, p = 0.0033; f² = 1.307) and has a very strong positive impact on Learning Motivation (? = 0.7078, T = 13.6517, p < 0.001; f² = 1.003). Learning Motivation also significantly influences Interest in Learning English (? = 0.4113, T = 2.6531, p = 0.0082; estimated f² ? 0.20). Additionally, Learning Motivation partially mediates the effect of Interactive Teaching Style on Interest in Learning English (indirect ? = 0.2911, T = 2.5027, p = 0.0126), confirming the dual pathways of influence. The results underscore the importance of interactive teaching methods in fostering student engagement and motivation, which in turn enhances their interest in learning English. This is particularly relevant for health science students who require strong language skills for clinical and academic purposes. It is recommended that STIKES Pelita Ibu Kendari optimize varied interactive teaching strategies emphasizing social interaction among students to bolster motivation and interest. Students should actively engage in collaborative and independent learning activities, while lecturers undergo ongoing professional development to master effective interactive and motivational teaching techniques.